Cold Regions Science and Technology - Cold Regions Science and Technology (Elsevier, 2026)
Cold Regions Science and Technology is an international journal dealing with the science and technical problems of cold environments in both the polar regions and more temperate locations. It includes fundamental aspects of cryospheric sciences which have applications for cold regions problems as well as engineering topics which relate to the cryosphere.
FI 0.76
Q1
Keywords: Earth; Space & Environmental Sciences; Environmental Science; Ciencia ambiental; Acuerdos transformativos; Transformative agreements; Criosfera; Glaciares; Hielo marino